Anthelmintic Potential Of Moringa Oleifera As Inhibitor Mitochondrial Rhodoquinol-Fumarate Reductase From Ascaris Suum Using The Docking Method - Dede Rival Novian (Universitas Muhammadiyah Magelang, 2019)
One of the parasitic nematodes that can cause malnutrition, even death in humans, is Ascaris suum. The parasite can survive in its host cell by metabolizing using the fumarate reductase enzyme. With this metabolism, the parasite can produce energy to survive in its host cell. Rhodoquinone (RQ) plays a part in helping the fumarate reductase reaction in parasite metabolism, and energy from metabolism was not produced when the enzyme was disrupted. Thus Mitochondrial rhodoquinol-fumarate reductase can be a good target of anthelmintic drug receptors. The results of investigations using in vitro and in vivo methods showed that Moringa oleifera has various medicinal functions including anti-inflammatory, antimicrobial, antidiabetic, antioxidant, anti-tumour, anti-cancer, and anti-clastogenic properties. However, the potential of the drug Moringa oleifera against anthelmintics has not been further investigated. Simulation docking is the research method used to find the anthelmintic potential of Moringa oleifera as the Ascaris suum inhibitor of Mitochondrial rhodoquinol-fumarate reductase. This study aims to examine the potency of Moringa oleifera bioactive compounds on the anthelmintic receptor Mitochondrial rhodoquinol-fumarate reductase by using efficient and effective research time with the docking simulation model. The results showed the bioactive compound 3,5-bis (1,1-dimethylethyl) -phenol from Moringa oleifera had potential as a new anthelmintic drug compound, 3,5-bis (1,1-dimethylethyl) -phenol activity had affinity energy of - 7.0 kcal / mol and has physicochemical properties that are not contrary to the rules of the drug compounds from Lipinski.